Primary School Pupils in Muranga County, Kenya Acquire Nutrition Knowledge and Enhance Iron Rich Food Consumption - Gitau, Gladys Njura; Kimiywe, Judith O.; Waudo, Judith N.; Gitau, Jimmy Ndungu (International Journal For Research In Health Sciences And Nursing, 2016)
Adequate nutrition knowledge lacks in school going children and it is in this light that this study was designed. The main objective of this study was to evaluate the effect of nutrition education on nutrition knowledge. A baseline survey was conducted in 12 randomly selected schools for 601 class six pupils and 67 households while 154 pupils participated at intervention. Questionnaires and an interview schedule were used to collect data with pre and post tests. Dietary intake was assessed. Baseline data were analyzed and on average, the mean mark in nutrition knowledge at baseline was 30.05% which was low. In the post-tests; all experimental schools significantly improved in nutrition knowledge and practices that enhance nutrition. Pupils Lacked of adequate nutrition knowledge and therefore the need for intervention strategies by all stakeholders in these settings. The study findings would contribute towards national school health policy and guidelines implementation to address malnutrition.